Ultra-high sensitivity detection of gold nanorods on a blotting membrane by laser induced desorption/ionization of gold ions. Issue 7 (9th February 2017) - Muko, Daiki; Inoue, Yuki; Nishitani, Atsushi; Niidome, Yasuro
Abstract : Laser induced desorption/ionization (LDI) of gold ions from gold nanoparticles was examined. The detection limit was estimated to be about 0.02 amol mm −2 . Abstract : Laser induced desorption/ionization (LDI) of gold ions from gold nanoparticles was examined. Gold nanorods showed more efficient LDI than that of spherical gold nanoparticles, where both materials had similar particle volumes. Large nanospheres (∼72 nm) showed more efficient LDI. The larger light absorption cross section of the nanoparticles at 355 nm contributed to efficient LDI. Mass signals from a blotting membrane were proportional to the extinction at corresponding spots. The ratio of the extinctions at 680 and 900 nm showed that aggregation of the nanoparticles suppressed the LDI efficiencies. Good-dispersion of the nanorods was an important factor for using them as a mass tag. The detection limit of the gold nanorods on a blotting membrane was estimated to be about 0.02 amol mm −2 . The outstanding potential of gold nanorods as a mass tag on a blotting membrane is clearly demonstrated.